Detection, prevalence and antibiotic susceptibility profile of vibrio species isolated from Epinephelus species in Peninsular Malaysia - Zulkiply, Nor Amalina (2021)
Infection of Vibrio species (spp.) among groupers (Epinephelus spp.) is one of the most reported diseases since it affects groupers’ production. Although it caused high mortality among groupers, a complete and up-to-date database on the prevalence and diversity of bacteria especially Vibrio spp. in groupers is not available in Malaysia. Thus, the objectives of this study were i) to characterize the bacterial diversity among cultured grouper and its culturing environment of seawater and sediment using a metagenomic approach, ii) to identify the prevalence and diversity of Vibrio spp. among cultured groupers in Peninsular Malaysia farms using the pyrH and gyrB genes, and iii) to determine the antimicrobial resistant profiles of Vibrio spp. In the metagenomic study, groupers’ liver, sediment and seawater samples were analyzed based on the 16S rRNA V3-V4 regions using the Illumina MiSeq platform. A total of 270 cultured groupers collected from nine farms in Peninsular Malaysia were used in the isolation and identification of Vibrio spp. based on the pyrH and gyrB genes. Then, the antimicrobial resistant profiles of Vibrio spp. isolates were determined using seven antibiotics such as ampicillin, penicillin, bacitracin, erythromycin, tetracycline, streptomycin and vancomycin. Results of the metagenomics test were generated 801,383 sequence reads and 9,308 operational taxonomic units (OTUs). The sediment showed the most diverse bacterial communities since it revealed the highest OTUs (7,378) compared to seawater (1,763) and liver of grouper (167). From the OTUs, phylum Proteobacteria was observed in the sediment (60%), seawater (54%) and liver (32%). Phylum Firmicutes was found only in the sediment and liver. Phylum Actinobacteria, Bacteroidetes, Cyanobacteria, Planctomycetes, and Chloroflexi were observed in sediment and seawater. Genus Vibrio and Photobacterium of phylum Proteobacteria were the only genera shared by the sediment, seawater and liver. Vibrio (77% - 96%) was dominantly present in the sediment and seawater compared to Photobacterium (2% - 7%). Similar Vibrio OTUs (denovo951 and denovo43955) were found in the sediment, seawater and liver indicating that there was a possible transmission of Vibrio between groupers and its surrounding environment. A study on the 270 cultured groupers collected from nine farms revealed that 380 Vibrio spp. were isolated from the pseudo-replicates of liver, spleen, and kidney of 195 (72%) cultured groupers. Results revealed that lesion was an early symptom of Vibrio infection since 82% of the cultured groupers were developed lesions on their skin, mouth and fins. A high number (25%) of the asymptomatic groupers were identified, thus, can be a Vibrio reservoir and threat to grouper farming. Vibrio spp. isolated from the groupers at the net cages was higher compared to the hatcheries. Analysis of the water quality is one of the contributor factors revealed that no correlation between the water quality parameters and increased number of Vibrio spp. at farms. Molecular analysis revealed that the pyrH gene was a superior phylomarker than the gyrB gene in identifying Vibrio spp. since it has high discriminatory power in differentiating species levels of Vibrio. Analysis of the phylogenetic tree of 380 pyrH sequences resulted in 13 Vibrio groups such as 28% of V. owensii, 25% of V. parahaemolyticus, 19% of V. alginolyticus, 14% of V. vulnificus, 3% of V. rotiferianus and Vibrio sp., 2% of V. campbellii, V. mytili and V. furnissii, and 1% of V. harveyi, V. diabolicus, V. fluvialis and V. tubiashii. Moreover, results revealed that groupers able to carry more than one Vibrio spp. simultaneously, thus, can enhance the mortality rate. Vibrio spp. also prone to infect the juvenile groupers rather than pre-adult groupers due to the immature immune systems developed. Analysis on the antimicrobial resistance profile suggested that ampicillin and penicillin G were ineffective in treating Vibrio infections since a high number (80%) of Vibrio spp. were resistant to both antibiotics. Effective monitoring on the administration of the bacitracin, erythromycin and vancomycin was required since 30% to 54% of the Vibrio isolates were found resistant to these antibiotics. Meanwhile, the resistance of Vibrio spp. to tetracycline and streptomycin was still low (14%). Most of the species included V. parahaemolyticus, V. alginolyticus, V. rotiferianus, V. campbellii and V. diabolicus were highly susceptible to both antibiotics. Multiple antibiotic resistance (MAR) index revealed that 88% of the Vibrio spp. had MAR index value of more than 0.2. Thus, the result indicated that the high number of Vibrio spp. were resistant to multiple antibiotics and continuously exposed to the antibiotics at the farms. Plasmid profiling results showed that 61% of Vibrio spp. were chromosomal-mediated with MAR index 0.37 and 39% were plasmid-mediated with MAR index 0.56. After the curing process, most of the Vibrio-positive plasmid were loss their resistance to antibiotics and the AMR index was reduced to 0.21. Thus, results indicated that the presence of problem can enhance the resistance of Vibrio spp. to antibiotics. In a conclusion, this study provided constructive documentation of bacterial communities in the groupers, sediment and seawater, prevalence of Vibrio infection among cultured groupers in Peninsular Malaysia, and occurrence of antibiotic resistance of Vibrio spp. presence in the cultured groupers.